2003
DOI: 10.1177/001440290306900306
|View full text |Cite
|
Sign up to set email alerts
|

Prereferral Intervention Processes: A Survey of State Practices

Abstract: Without a federal mandate providing clear guidelines for specific practices, prereferral intervention practices are implemented in varied ways within and between the states. The current study focused on practices across all states as a replication of the research reported in 1989 by Carter and Sugai. Significant findings included the status of prereferral practices within the respective states, the pattern of terminology used, the professional ownership of the process, and the patterns of participation. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 9 publications
4
50
1
Order By: Relevance
“…This is consistent with the findings of Buck et al (2003). For example, only 14% of the states made any recommendations about PIT membership.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with the findings of Buck et al (2003). For example, only 14% of the states made any recommendations about PIT membership.…”
Section: Discussionsupporting
confidence: 90%
“…The current research confirms previous findings that prereferral intervention is commonly required or recommended by states (Carter & Sugai, 1989), preferably via team-based approaches (Buck et al, 2003). The current research confirms previous findings that prereferral intervention is commonly required or recommended by states (Carter & Sugai, 1989), preferably via team-based approaches (Buck et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…They reported that 43% of the states required prereferral intervention practices, whereas an additional 29% recommended the use of such practices. Numerous states (47%) reported not using a standard term statewide for the team; however, the most common terms were child study team, prereferral intervention team, and teacher intervention team (Buck et al, 2003).…”
Section: Historical Evolution Of Teams In Schoolsmentioning
confidence: 99%
“…In a survey of state departments of education, Buck, Polloway, Smith-Thomas, and Cook (2003) found that almost half (49%) of the respondents indicated that their intervention teams were led by school administrators or student service coordinators. In a survey of state departments of education, Buck, Polloway, Smith-Thomas, and Cook (2003) found that almost half (49%) of the respondents indicated that their intervention teams were led by school administrators or student service coordinators.…”
Section: References To Administrative Participation In Teams In the Lmentioning
confidence: 99%